The Influence of Service Quality (Servqual) on the Satisfaction of BPJS Patients in Indonesian Healthcare Facilities: A Systematic Review - Novita Yudiana Pangaribuan; Vanessa Vanessa; Jonathan Juniard Anurantha (Journal Research of Social Science, Economics, and Management, 2025)
The increasing number of BPJS users is not always accompanied by improvements in service quality, leading to varied patient experiences and satisfaction levels. This study aims to analyze and synthesize empirical evidence on the influence of the five SERVQUAL service quality dimensions—reliability, assurance, tangibility, empathy, and responsiveness—on BPJS patient satisfaction in Indonesian health facilities. Therefore, a systematic review is needed to comprehensively examine this influence. This study employs a systematic review method to explore the relationship between health service quality and BPJS patient satisfaction, based on the five service quality dimensions (reliability, assurance, tangibility, empathy, and responsiveness) at facilities such as hospitals and community health centers (Puskesmas). The review was conducted using the Google Scholar database. The five SERVQUAL service quality dimensions (reliability, assurance, tangibility, empathy, and responsiveness) generally show a significant positive relationship with BPJS patient satisfaction in Indonesian health facilities. Although the most influential dimension varies across studies, overall improvements in service quality across all dimensions directly contribute to higher patient satisfaction. Based on the nine studies analyzed, the five SERVQUAL service quality dimensions (reliability, assurance, tangibility, empathy, and responsiveness) generally have a significant relationship with BPJS patient satisfaction.